Hubungan Indeks Massa Tubuh (IMT) dengan Tingkat Keparahan Disminore - Indraswari Siscadarsih; Rizqi Amanullah; Wafda Ardhian Latansyadiena (Poltekkes Kemenkes Palu, 2022)
Introduction: Several studies have shown that women who have overweight and obese tend to have more severe dysmenorrhea than women with a normal BMI. The results of the preliminary study that have been carried out, obtained information that students who lived in the Yogyakarta Ministry of Health Poltekkes dormitory for more than six months have a prevalence of underweight of 20.13% and overweight of 25.62%. Purpose: The purpose of this study was to determine the relationship between BMI and the severity of dysmenorrhea. Methods: This research is quantitative using primary data sources with a cross-sectional design. The sample in this study were students of the Department of Midwifery. Sampling using non-probability sampling method by purposive sampling as many as 311 people. Result: The analysis of this study was carried out using multivariate. The results of this study indicate that there is a significant relationship between BMI and dysmenorrhea (p=0.006). In respondents with dysmenorrhea, the OR for having severe dysmenorrhea in obese respondents was 6.3 times, compared to respondents with normal weight. Conclusion: BMI in adolescents with obesity affects the severity of dysmenorrhea so physical activity and nutritional intake need to be considered to reduce body weight.